2013
DOI: 10.5750/jgbe.v5i1.562
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Consumers' Participation in Gambling Markets and Frequency of Gambling

Abstract: Survey data on participation in gambling typically contain many zeros. The presence of many zeros presents methodological problems for the analysis of participation in gambling markets and gambling expenditure. The most common techniques for handling zeros in gambling data have been the Tobit estimator and the Heckman selectivity estimator. Recent research indicates that hurdle models (Jones 1989, 2000) and the Cragg (1971) model, are better suited to analyze participation in gambling. We apply these models to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This is not unexpected at all, but actually consistent with existing research. 13,15 When addressing interdependencies and time preferences for smoking, drinking, and gambling, research founds that the more education, the less time preference for gambling and therefore likelihood of addiction. 8 In fact, it is concluded that “governments might consider education as an effective countermeasure for stopping addictions.” 8…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not unexpected at all, but actually consistent with existing research. 13,15 When addressing interdependencies and time preferences for smoking, drinking, and gambling, research founds that the more education, the less time preference for gambling and therefore likelihood of addiction. 8 In fact, it is concluded that “governments might consider education as an effective countermeasure for stopping addictions.” 8…”
Section: Resultsmentioning
confidence: 99%
“…These are common covariates in gambling research, as gambling patterns and behavior are strongly determined by socio-demographic and health conditions. 9,13,16,17,18 Individuals who failed to respond to our key variables were removed from the sample, as were observations with encoding errors. All in all, 199 individuals were dismissed (2.92% of the sample), so 6617 remained.…”
Section: Data and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Wicker and Soebbing (2012), this study found an inverted u-shaped link between age and the probability that a respondent had already participated in sports betting. Because some earlier researchers (Humphreys et al, 2011) report evidence of a nonlinear age effect this study analysed the age effect with splines in more detail and could confirm the presence of a nonlinear effect.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…These runners, albeit treated as non-spenders on TOUR, had "a potential level of consumption" (Eakins, 2018, p.165). Given the way non-spenders on TOUR were defined, the Heckman model was considered appropriate (Humphreys, Lee, & Soebbing, 2011;Jones, 2000).…”
Section: Discussionmentioning
confidence: 99%